How to Define a Genre: A Lacanian-marxist Case Study of the NES Platform Game - Skare, Nils (Eludamos: Journal for Computer Game Culture, 2011)
This article’s purpose is to define the NES platform game as a specific genre through a materialist approach. Discarding both inductive and deductive ways, we select two games that can be said to be extreme translations of the genre and thus derive the concept from their analysis: the games are Super Mario Bros. 3 (SMB3) and Mega Man 2 (MM2). This article develops concepts from our materialist framework, notably the Lacanian Borromean knot and derived semiotics, and our own definition of narrative as a symbolic predication of the Real. After analyzing our games and establishing a model, we relate SMB3 to identification and MM2 to recognition, and define the NES “platformers” as games where there is at least one metaphorical non-jump button.